Tocopherol content, peroxide value and sensory attributes in roasted peanuts during storage - Silva, Mercedes Pilar; Martinez, Maria Jose; Casini, Cristiano; Grosso, Nelson R. (2017)
The objective of this study was to determine changes in tocopherol content, peroxide value (PV) and sensory attributes from roasted peanuts during storage at 40 °C. There were no differences in tocopherol contents between roasted and raw peanuts except in α-tocopherol content that decreased after roasting. All tocopherol contents decreased during storage. On the contrary, lipid oxidation indicators such as PV and the intensity ratings of oxidised and cardboard flavour increased during storage. On the other hand, the intensity ratings of roasted peanutty flavour decreased with storage time. Good correlations were observed between tocopherol contents and PVs. Tocopherol contents could be used as indicator of oxidative state in peanut products.